Using Simultaneous Structures to Cope With Uncertainty - McDonough, Edward F.; Leifer, Richard (Academy of Management Journal, 1983)
The article discusses a study pertaining the corporate use of simultaneous structures in work units to cope with uncertainty. A work unit in this context refers to a supervisor and their subordinates, all of whom perform related tasks. The research indicated that supervisors rely on multiple structures in order to carry out the different tasks of the work unit. It is believed that a supervisor's use of a particular structure may depend on their personal preference or their perception of the employees' decision making ability.